Transformation of the roles and tasks of management accountants in a Malaysian organization / Zairul Nurshazana Zainuddin, Suzana Sulaiman and Sharifah Fadzlon Abdul Hamid - Zainuddin, Zairul Nurshazana; Sulaiman, Suzana; Abdul Hamid, Sharifah Fadzlon (Universiti Teknologi MARA Cawangan Selangor, 2014)
The roles and tasks of management accountants have evolved overtime. In the past, management accountants were known as information providers normally involved in supporting, controlling, communicating and coordinating organisational activities. The current scenario however, indicates that their roles and tasks have extended to include forecasting and analysing business performance in pursuit of providing timely information to assist the board members in forming quality decisions. Moving forward, the roles and tasks of management accountants are expected to transform with the changes in the expectations of stakeholders and competitive environments. This case study is carried out to examine the past and future roles and tasks of management accountants in a Malaysian organisation. An extensive interview was conducted, and the findings show that the roles of management accountants have transformed and will continue to transform to facilitate the changes in the global business environment. From being information providers, management accountants are becoming value creators and strategists. Factors that caused these changes are both internal and external to organisations.